Indonesia’s Crude Palm Oil (CPO) Export Dynamics: A 2000–2024 Perspective - Martalita, Nadia Lasa; Robiani, Bernadette; Rohima, Siti; Yulianita, Anna (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2025)
Indonesia is the world’s leading exporter of palm oil, fulfilling approximately 52% of global demand. The export of Crude Palm Oil (CPO) serves as a strategic component of the country's agro-based industry and remains the largest contributor to non-oil and gas foreign exchange earnings. Despite its significance, there remains limited empirical research examining the impact of Foreign Direct Investment (FDI), Domestic Investment (DI), and the exchange rate on Indonesia’s CPO export value, particularly over the period 2000 to 2024. This study aims to fill that gap by employing secondary time series data sourced from the World Bank, Statistics Indonesia (Badan Pusat Statistik), and Bank Indonesia. The research applies a multiple linear regression analysis using the EViews 12 statistical software. The results reveal that FDI has a positive and statistically significant effect on Indonesia’s CPO export value. In contrast, Domestic Investment and the exchange rate show no significant partial influence. However, when analyzed simultaneously, FDI, DI, and exchange rate collectively exert a significant impact on CPO export performance. Furthermore, the analysis of export value trends from 2000 to 2024 shows a generally positive trajectory, highlighting the continued importance of policy support and investment in maintaining Indonesia's dominance in the global palm oil market.